RELATIVE AGE EFFECT IN PROFESSIONAL SOCCER ATHLETES DURING 2005' CONFEDERATIONS CUP GERMANY. (Fiep Bulletin - online, 2015)
Age differences among individuals of the same age group or “school-year” is called relative age and its consequence is called Relative Age Effect - RAE (Musch and Grondin, 2001). The use of elements based on RAE has been observed in soccer, mainly in youth categories, and it is even more intense as early the category is. The aim of this study was to verify the frequency of RAE in professional soccer players who participated in Confederations Cup  Germany, promoted by FIFA in July, 2005. Birth dates of all 184 soccer players (26.85 ± 3.49 years old) from 8 selections participating in 2005' Confederations Cup  Germany were considered for this study. The athletes were divided into 2 categories: first semester and second semester according to birth date. Analysis for binomial non-parametric tests through SPSS 13.0 software was applied with “test proportion” set in 0.50 and p = 0.05. Although extreme values have been observed in two national teams, no differences were found among the national teams, suggesting that the RAE is a phenomenon restricted to youth categories. We conclude that the adoption of criteria related to relative age in youth categories without considering the other variables involved in the process of athletes development is inadequate, leading to a possible non-selection of young athletes with a high technical potential.
Keywords: .